Biblical Aramaic Passive Stems: A Re-examination of Some Intriguing Cases - Mastey, Emmanuel (Aramaic studies, 2022)
Perfect verbs in the Passive-Qal (qetil) and Hufʿal (huqtal or hoqtal) stems are attested in both Biblical (BA) and Middle Aramaic. This paper contests the claim of BA grammars that the Hufʿal imperfect is unattested in BA. Moreover, some scholars have doubted the authenticity of the Masoretic vocalisation of some Hufʿal and Passive-Qal occurrences, postulating that the Hufʿal preformative vowel was changed from a to u under the influence of the Hebrew Hufʿal. This paper discusses the most problematic occurrences from morphological, syntactic, and contextual viewpoints, and concludes that the Masoretic vocalisation of the forms in question is generally reliable. Lastly, a form that was mistakenly identified as a disguised Passive-Qal form is shown to be a Qal (active) form. It appears that the marking of human direct objects by lamed accusativi in BA has fewer exceptions than previously thought.